Penerapan Kaidah Majaz Mursal dalam Al-Qur’an: (Kajian Balagah mengetahui Struktur dan Fungsinya dalam Penafsiran al-Qur’an) - Raudatul Jannah; Achmad Abubakar; Muhammad Irham; Anggun Puspita Ningrum; Sri Virnawati (Al-Aqwam: Jurnal Studi Al-Quran dan Tafsir, 2025)
This article aims to analyze the interpretation of the Qur’an using the language style of majaz, especially in majaz mursal. Because the language style of majaz influences, expands the meaning of the word arrangement in the Qur’an and the understanding of the meaning desired by Allah swt, has implications for translation and interpretation, several verses of the Qur’an are interesting both in terms of sentence composition and rhetoric (balaghiyyah) this study uses a descriptive method of analysis of majaz mursal in verses of the Qur'an, both in different contexts and themes. This study uses methods from qualitative data sources. This application shows the richness of language and depth of thought in sacred texts, and invites people to better understand Islamic teachings holistically.